In the maelstrom : the Waffen-SS "Galicia" Division and its legacy - Shkandrij, Myroslav, 1950- (McGill-Queen's University Press, 2023)
"An estimated 25,000 Ukrainians served in the Fourteenth Waffen-SS "Galicia" Division. Conflicting accounts of their reasons for enlistment and continuing accusations of wartime criminality have fuelled controversial debate for decades. The first comprehensive study of the Division to address both the military formation's wartime experience and its postwar fate, In the Maelstrom draws on archival research that includes interrogation records, interviews, memoirs, testimonies, and creative literature. The accounts of veterans often begin with being drafted for the force in teenage years and continue into postwar life in Italian and British internment camps. These reminiscences are compared with wartime records and recent narratives. The book then discusses the commissions of enquiry into war crimes during the 1980s, recent debates over the issue of monuments and commemoration, and different ways in which veterans, the diaspora community, Western governments, and researchers have approached the topic. In the Maelstrom brings to light the underexplored Ukrainian experience in the "Galicia" Division during and after the war. Due to the 2022 Russian invasion of Ukraine, this experience resonates strongly today."--